EXPLORING INDONESIAN EFL LEARNERS’ METAFUNCTION COMPETENCE AND THEIR CRITICAL READING - Nani Ronsani Thamrin; Jaruki Andriansyah Maulana (Indonesian EFL Journal, 2015)
This study explores the relationship between students’ metafunction competence and their critical reading. This study uses mixed method approach to discover deep and whole comprehension of the research problem. The five undergraduate students who have attended functional grammar class are purposively involved. This study shows that students’ metafunction competence and their critical reading positively correlate. In the other words, the students’ metafunction competence develops their critical reading ability. It is corresponding with the conclusion which is drawn by Bumela (2011) that the initial formation of meaning is also largely influences by reader’s expectations and background knowledge. Hereby, students’ metafunction competence plays as students’ background knowledge to recognise the features of the texts and identify the metafunctions of the texts which is beneficial as the departure for critical reading.Keywords: students’ metafunction competence, critical reading.